TRAINING OF FUTURE EDUCATORS TO THE DEVELOPMENT OF THE EMOTIONAL INTELLIGENCE OF CHILDREN OF OLDER PRESCHOOL AGE - Skomorovska, Iryna; Matishak, Marianna (Mountain School of Ukrainian Carpaty, 2023)
The article reveals the problem of professional training of future preschool teachers for the development of emotional intelligence in children of older preschool age. Several definitions of the concepts of «emotions» and «emotional intelligence» are presented. It is noted that emotional intelligence is interpreted as a set of mental abilities to understand one's own emotions and the emotions of other people, as well as managing the emotional sphere. D. Goleman. The components of emotional intelligence presented by scientists are characterized, namely: awareness and recognition of feelings; the desire to understand another person; understanding emotions; managing emotions. An analysis of the emotional development of older preschool children was carried out, in particular, it was indicated that they are characterized by wide social contacts, namely parents, educators, pupils from kindergarden, friends at the place of residence, etc. As a result of the existing wide circle of communication, preschoolers are often in interaction with others, which requires from them the ability to express their own emotions and understand the emotions of other people. It is emphasized that a child of older preschool age is able to understand such emotions of others as joy, surprise, sadness, anger, irritation, fear, etc. It has been proven that the teacher plays a significant role in the emotional development of preschoolers. In order to effectively carry out the outlined activities, the training of future teachers of preschool education institutions should include the following components: cognitive (mastery of professional knowledge and competences), motivational (motivation to interact with children and the presence of a desire to implement professional activities), activity component (set of practical skills and abilities , which are necessary for successful work with preschoolers). It is noted that in order to develop the emotional intelligence of older preschoolers, it is expedient for future preschool educators to organize the following types of activities: reading the books with further analysis of the emotions and feelings of various characters; carrying out game exercises of the corresponding topic; organization of various types of theatrical activities, etc.